2023
DOI: 10.1177/17562848231196357
|View full text |Cite
|
Sign up to set email alerts
|

Empirical versus tailored therapy based on genotypic resistance detection for Helicobacter pylori eradication: a systematic review and meta-analysis

Meng Li,
Xiaolei Wang,
Wenting Meng
et al.

Abstract: Background: The eradication rate of Helicobacter pylori infection with empirical therapy has decreased due to increased drug resistance. The latest guidelines recommend genotypic resistance-guided therapy, but its clinical efficacy remains unclear. Objectives: The purpose of our study was to evaluate whether tailored therapy based on genotypic resistance is superior to empirical therapy for H. pylori infection. Design: A systematic review and meta-analysis of randomized controlled trials (RCTs) comparing tailo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 40 publications
0
0
0
Order By: Relevance
“…In the near future, a shared approach, with concentration on clinical cases in a few expert centers, will be of paramount importance to ensure quality in H. pylori eradication, as already confirmed by evidence of similar experiences in other fields [37]. Furthermore, it is appropriate that clinical trials for H. pylori treatment will be supported by resistance information; this approach will be pivotal in order to reach, whenever possible, a basis for the formulation of a tailored therapy taking into account individual antimicrobial resistance profiles [38][39][40][41][42][43].…”
Section: Discussionmentioning
confidence: 92%
“…In the near future, a shared approach, with concentration on clinical cases in a few expert centers, will be of paramount importance to ensure quality in H. pylori eradication, as already confirmed by evidence of similar experiences in other fields [37]. Furthermore, it is appropriate that clinical trials for H. pylori treatment will be supported by resistance information; this approach will be pivotal in order to reach, whenever possible, a basis for the formulation of a tailored therapy taking into account individual antimicrobial resistance profiles [38][39][40][41][42][43].…”
Section: Discussionmentioning
confidence: 92%
“…For genotypesusceptible strains, the pooled eradication rate with targeted antibiotics was 93.1% (95% CI:91.3-94.9%) [81]. Moreover, a recent meta-analysis demonstrated that molecular method-guided therapy is more efficacious than empirical therapy when used as triple therapy (not as quadruple therapy) [29].…”
Section: Clinical Applications Of Genotypic or Molecular-based Methodsmentioning
confidence: 99%
“…Thus, H. pylori eradication should be guided by antibiotic susceptibility testing (AST), preferably by genotypic methods. Indeed, a recent meta-analysis enrolled 12 qualified randomized controlled trials containing 3940 patients clearly demonstrated that the pooled eradication rates of tailored therapy based on the detection of genotypic resistance were consistently higher than those in the empirical treatment group [29].…”
Section: Importance Of Detecting Antibiotic Resistance In H Pylorimentioning
confidence: 99%